Binding by the Hepatitis C Virus NS3 Helicase Partially Melts Duplex DNA - Raney, Veronica M. (2012)
Binding of NS3 helicase to DNA was investigated by footprinting with KMnO(4), which reacts preferentially with thymidine residues in ssDNA compared to those in dsDNA. A distinct pattern of reactivity was observed on ssDNA, which repeated every 8 nt and is consistent with the known binding site size of NS3. Binding to a DNA substrate containing a partial duplex was also investigated. The DNA contained a 15 nt overhang made entirely of thymidine residues adjacent to a 22 bp duplex that contained thymidine at every other position. Surprisingly, the KMnO(4) reactivity pattern extended from the ssDNA into the dsDNA region of the substrate. Lengthening the partial duplex to 30 bp revealed a similar pattern extending from the ssDNA into the dsDNA, indicating that NS3 binds within the duplex region. Increasing the length of the ssDNA portion of the partial duplex by 4 nt resulted in a shift in the footprinting pattern for the ssDNA by 4 nt which is consistent with preferential binding to the 3’-end of the ssDNA. However, the footprinting pattern in the dsDNA region was shifted by only 1–2 bp, indicating that binding to the ss/dsDNA region was preferred. Footprinting performed as a function of time indicated that NS3 binds to the ssDNA rapidly, followed by slower binding to the duplex. Hence, multiple molecules of NS3 can bind along a ss/ds DNA partial duplex by interacting with the ssDNA as well as the duplex DNA.